Enhancement of Rydberg-mediated single-photon nonlinearities by electrically tuned Förster resonances - H. Gorniaczyk (Nature Portfolio, 2016)
Single photon level of light control is possible by using the effective interaction between single photons and Rydberg atoms. Here the authors utilized such interaction of Stark-tuned Forster resonances to boost the gain of a Rydberg single-photon transistor and perform high precision spectroscopy.